Osteogenic molecules for clinical applications: Improving the BMP-collagen system - Arrabal-García, Pilar María; Visser, Rick; Santos-Ruiz, Leonor; Becerra-Ratia, José; Cifuentes-Rueda, Manuel (Sociedad de Biología de Chile, 2013)
Among the osteogenic growth factors used for bone tissue engineering, bone morphogenetic proteins (BMPs) are the most extensively studied for use in orthopaedic surgery. BMP-2 and BMP-7 have been widely investigated for developing therapeutic strategies and are the only two approved for use in several clinical applications. Due to the chemical and biological characteristics of these molecules, their authorised uses are always in combination with a carrier based on collagen type I. Although the use of these growth factors is considered safe in the short term, the very high doses needed to obtain significant osteoinduction make these treatments expensive and their long-term safety uncertain, since they are highly pleiotropic and have the capacity to induce ectopic ossification in the surrounding tissues. Therefore it is necessary to improve the currently used BMP-collagen system in terms of efficiency, biosecurity and costs. There are several strategies to increase the clinical effectiveness of these treatments. In this review we summarize the most promising results and our related work focused on this field through two different approaches: i) the development of recombinant BMPs with additional features, and ii) complementing these systems with other growth factors or molecules to enhance or accelerate osteogenesis.
Keywords: Huesos - Crecimiento; BMPs (Bone Morphogenetic Proteins); BMP2; Growth Factors; FGFs (Fibroblast Growth Factors); FGF2; Recombinant proteins; Osteogenesis; RGD Peptide; Delivery Systems; Binding domains; Mesenchymal Stem Cell (MSC); Open tibial fracture; Spinal fusion; Fusion protein